EDUKASI DIGITAL SEBAGAI STRATEGI MEDIA PEMBELAJARAN - Salman (Jurnal Payung Sekaki : Kajian Keislaman, 2024)
With the development of social media, performance becomes faster, more precise and accurate, which ultimately increases productivity. One of the current social media users is students. The reason is, social media allows students to easily communicate at close or long distances without having to meet face to face. Not only is social media important for students to stay informed, it can also improve critical thinking and develop work-related skills and creativity. The aim of this research is to determine the use of social media as a learning medium. This research uses a data analysis method that focuses on library research by reading, studying and surveying books and literary materials that are closely related to the research questions. The use of social media in learning media can further improve the quality of learning if used as comprehensively as possible. However, this does not mean that social media will have a negative impact if its use is not controlled and the information is not filtered. Mistakes may occur during the learning process if teachers do not use social media as a teaching medium properly.